Heterogeneous structural changes correlated to local atomic order in thermal rejuvenation process of Cu-Zr metallic glass - Masato Wakeda (Science and Technology of Advanced Materials, 2019)
In this study, we investigated the atomistic mechanism of structural excitation in a thermal process (thermal rejuvenation) of metallic glass. In a molecular dynamics framework, Cu-Zr metallic glass was rejuvenated by a thermal process composed of an isothermal heat treatment at a temperature above the glass transition temperature $${T_{\rm{g}}}$$, followed by fast cooling. Atomistic analyses of the local rearrangement, potential energy, and geometrical structure revealed structural changes correlating to the local atomic order in the rejuvenation process. In the early stage of the heat treatment for thermal rejuvenation, the structural excitation exhibited spatial heterogeneity at the nanometer scale. More-excited regions (i.e., regions with large atomic non-affine and affine transformations) exhibited low-ordered structures and vice versa, implying that the local structural excitation is significantly correlated with the local atomic order. The structural excitation transitioned from partial to whole as the isothermal process proceeded above $${T_{\rm{g}}}$$. Although rejuvenation decreased the ordered structure, the calculation results suggested the formation of newly ordered local structures and newly disordered local structures correlated to local structural excitations and atomic dynamics in the thermal process. These results indicate that the heterogeneous structure evolution of the rejuvenation process induces a redistribution of the local atomic order in the microstructure of metallic glasses.